Belize : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper describes economic developments in Belize during the 1990s. Economic activity slackened in 1993-97, with a sharp slowdown in domestic investment and a sluggish performance of services following the withdrawal in 1994 of the United Kingdom garrison that had been stationed in Belize. Investment fell from its peak of 32 percent of GDP in 1993 to 23 3/4 percent of GDP in 1997 as both public and private capital formation declined, and national savings fell from 23 percent of GDP in 1993 to 18 percent of GDP in 1997.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet